Respuesta :
Step 1: Simplify both sides of the equation.
6h+42=84
Step 2: Subtract 42 from both sides.
6h+42−42=84−42
6h=42
Step 3: Divide both sides by 6.
6h6=426
h=7
hope this helped!!☺
6h+42=84
Step 2: Subtract 42 from both sides.
6h+42−42=84−42
6h=42
Step 3: Divide both sides by 6.
6h6=426
h=7
hope this helped!!☺
Hey there! :)
If you switch it around, it becomes: 84 - 42 = 6h
84 - 42 = 42
42 = 6h
Divide both sides by 6
42 ÷ 6 = 7
6h ÷ 6 = h
7 = h
Hope this helps :)
If you switch it around, it becomes: 84 - 42 = 6h
84 - 42 = 42
42 = 6h
Divide both sides by 6
42 ÷ 6 = 7
6h ÷ 6 = h
7 = h
Hope this helps :)